The role of corporate culture in economic development of small and medium-sized enterprises - Lorincová, Silvia; Miklošík, Andrej; Hitka, Miloš (Technological and Economic Development of Economy, 2022)
Achieving economic development of the enterprise is enabled by the efficient use of resources, efficient processes and, last but not least, a suitable corporate culture. Under the influence of a dynamically changing business environment, corporate culture is gaining in importance and justification. It needs to be monitored and evaluated together with “hard” business indicators. The research explores the key values that should be applied in corporate culture at the strategic level to support the economic development of small and medium-sized enterprises. The differences between small and medium-sized enterprises operating in the industrial sector in Slovakia are defined. As managers have a direct impact on the creation of corporate culture, their preferences regarding corporate culture are examined, using the methodology of Cameron and Quinn. The results of the research prove the preference for applying key values typical for a clan culture. Following the results, it is recommended managers to focus on supporting a clan culture that develops employees. It is the employees who create and build values, bring new, innovative ideas, and with their abilities and skills influence the performance, competitive advantage, economic development, and success of the entire enterprise as well as economic development of small and medium-sized enterprises.First published online 02 December 2021